STUDI EKSPLORATIF TENTANG KEPUASAN KERJA DAN RETENSI KARYAWAN DI INDUSTRI MANUFAKTUR: STUDI KASUS PADA PT PRICOL SURYA INDONESIA - Silvia; Uus Mohammad Danil Fadli (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted to explore the factors that influence job satisfaction and employee retention at PT Pricol Surya Indonesia, a manufacturing company operating in Indonesia. The background of the study includes the importance of understanding these factors in the context of a competitive manufacturing industry. The purpose of the study is to identify and analyze working conditions, interpersonal relationships, career development opportunities, and company policies as key variables that influence job satisfaction and employee retention. The research method used is a qualitative approach using in-depth interviews with employees in various departments of the company. The study results show that good working conditions, positive interpersonal relationships, clear career development opportunities, and transparent company policies are the main factors in improving job satisfaction and employee retention. Based on these findings, suggestions include improving working conditions, strengthening interpersonal relationships, increasing career development opportunities, and implementing fair company policies to improve employee well-being and organizational stability